Highly Efficient Visible Light Assisted Synthesis of Perimidines under Catalyst-free and Room Temperature Conditions - Agarwal, Shikha; Patel, Isha; Sahiba, Nusrat; Soni, Jay (Letters in Organic Chemistry, 2023)
Visible light has come to the fore in organic chemistry as a cheap and readily available energy source. Energy transfer reactions represent the future directions for the development of practical and scalable industrial reactions with several environmental benefits. A facile, economic, and visible light (CFL) induced synthesis of perimidines has been established through a cyclo-condensation reaction of 1,8-diaminonaphthalene and aryl aldehydes with excellent yields (87-100%) in a short span of time. The present method has several merits a highly efficient, greener, high atom economy, no need of external heating and other instrumental setups, no need for a catalyst, and no tedious purification process.
Keywords: catalyst-free